2011
DOI: 10.1007/s11249-011-9867-6
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Mechanism of Perfluoropolyether Lubricant Film with Functional Endgroup on Magnetic Disks by Ultraviolet Irradiation

Abstract: We studied the bonding mechanism of ultrathin perfluoropolyether (PFPE) lubricant (Fombline Z-tetraol and Moresco D-4OH) films with hydroxyl end groups by measuring the bonding film thickness after ultraviolet (UV) irradiation. Nonfunctional PFPE lubricants (Z-03 and D2 N) were compared to two types of functional PFPE lubricants. The bonded thickness of both functional lubricants increased after a short period of UV irradiation, whereas that of the nonfunctional lubricants did not increase after the same treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Bonding of PFPE type lubricant on the hard disk surface could also be enhanced upon a short period of UV irradiation, depending on the end group of PFPE. The presence of hydroxy group facilitates the formation of stronger bonding than PFPE lubricant without terminal polar group due to the occurrence of selective dissociation of the end groups after UV irradiation as well as subsequent interaction between lubricant and hard disk surface …”
Section: Resultsmentioning
confidence: 99%
“…Bonding of PFPE type lubricant on the hard disk surface could also be enhanced upon a short period of UV irradiation, depending on the end group of PFPE. The presence of hydroxy group facilitates the formation of stronger bonding than PFPE lubricant without terminal polar group due to the occurrence of selective dissociation of the end groups after UV irradiation as well as subsequent interaction between lubricant and hard disk surface …”
Section: Resultsmentioning
confidence: 99%
“…This indicates that these profiles are mainly formed by the movement of lubricant and plastic deformation. Figures 5,6,and 7 show protuberances at the beginning of the wear test and grooves at the end, for the A20H, D-4OH, and 1.6 nm thick Z-tetraol samples, respectively. Figure 8 shows that the entire protuberance profile for the 2.6 nm thick Z-tetraol sample is like a gently sloping hill.…”
Section: Resultsmentioning
confidence: 99%
“…Perfluoropolyether (PFPE) is a polymer consisting of carbon, oxygen, and fluorine. Functionalized PFPE lubricants have been investigated to improve the retention and replenishment of the lubricant on DLC films [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the ultraviolet (UV) irradiation process is generally used to obtain highly chemically bonded lubricant films. Tani et al [8] suggested the occurrence of three kinds of mechanisms on the normal UV process for magnetic disks. First, PFPE lubricants bond to the DLC surface because of the photodissociation of the end groups by the UV light.…”
Section: Introductionmentioning
confidence: 99%